Case report: Left atrial myxoma with morphology of cavernous hemangioma supplied by the right coronary artery - Zhang, Shouji; Wang, Junlin; Song, Fahang; Yang, Fan; Li, Fang; Liu, Shangxin; Ma, Jiwei; Zhang, Haizhou; Ma, Xiaochun (Frontiers in Cardiovascular Medicine, 2023)
Here we reported an unusual case of left atrial myxoma presented with morphology of cavernous hemangioma supplied by the right coronary artery. Surgical resection of the left atrium myxoma was performed and the patient experienced an uneventful recovery during hospitalization.